2021
DOI: 10.1186/s12893-021-01421-x
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of massive tibial defect caused by osteomyelitis using induced membrane followed by trifocal bone transport technique: a retrospective study and our experience

Abstract: Objective To evaluate clinical outcomes of the application of induced membrane followed by trifocal bone transport technique in the treatment of massive tibial defect caused by osteomyelitis. Method A total of 18 eligible patients with tibial defect > 6 cm caused by osteomyelitis who were admitted to our institution from January 2010 to January 2016 and treated by induced membrane followed by trifocal bone transport technique. There were 12 male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…The initial search identified 1251 publications. Twenty-three of these met the eligibility criteria for the pooled analysis, including 1153 patients treated by distraction osteogenesis [ 8 , 12 , 14 , 15 , 22 28 , 31 42 ]. Details of each study are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial search identified 1251 publications. Twenty-three of these met the eligibility criteria for the pooled analysis, including 1153 patients treated by distraction osteogenesis [ 8 , 12 , 14 , 15 , 22 28 , 31 42 ]. Details of each study are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies in the observed group reported the use of either poly-methyl methacrylate or calcium sulphate bone cement within the defect (54 patients) [ 22 , 37 ]. The rationale for this is to induce a biologically active membrane to assist union and regenerate formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination of Masquelet technique (induced membrane technique) followed by Ilizarov bone transport demonstrated effectiveness in the treatment of nonunions of long bones [ 51 , 52 ]. The bone transport through induced membrane chamber allowed improving outcomes and avoiding bone grafting.…”
Section: Discussionmentioning
confidence: 99%
“…In addressing this concern, a range of therapeutic approaches have been recognized as efficacious. Autologous bone grafts, the induced membrane technique, the Ilizarov method (based on distraction osteogenesis principles), and vascularized and nonvascularized fibular grafting techniques are among the methodologies that can be implemented [ 5 13 ]. Determining the most appropriate treatment strategy is contingent upon a multitude of crucial considerations, encompassing the defect’s precise site and extent, as well as any additional injuries.…”
Section: Introductionmentioning
confidence: 99%